Perovskite ink, perovskite thin film and battery device

By adding nucleation regulators to the perovskite ink, the aggregation barrier of perovskite nucleation is reduced, and the impurity phase and defects in perovskite film are solved, thus achieving a more uniform perovskite film preparation and improving The efficiency and stability of perovskite solar cells are achieved.

CN119432148APending Publication Date: 2025-02-14YUNNAN UNIV +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411539979.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

In mixed cation and anion systems, realizing pure phase and uniform perovskite films is a key issue in improving device efficiency and operating stability. In the prior art, perovskite films are prone to multi-scale defects, such as point defects and elemental segregation. , equal impurities affect photovoltaic performance and long-term stability.

Method used

A perovskite ink is provided, and its components include a formidinyl perovskite material, a coordination solvent and a nucleation regulator. By reducing the aggregation barrier of the perovskite nucleation, the obtained perovskite wet film is prepared only. It contains pure perovskite alpha phase, inhibits the generation of impurity phases, and obtains a more uniform perovskite film.

Benefits of technology

By using nucleation regulators, the repulsion interaction energy is significantly reduced, the aggregation barrier of perovskite films is lower, and the prepared perovskite film is more uniform, suitable for large-area film preparation, improving the electrochemical performance of battery devices and stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119432148A_ABST
    Figure CN119432148A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of perovskite solar cells, in particular to perovskite ink, a perovskite thin film and a cell device, and the perovskite ink comprises a formamidino perovskite material, a coordination solvent and a nucleation regulating agent. The aggregation potential barrier of perovskite nucleation in the perovskite ink is low, the prepared perovskite wet film only has a pure perovskite alpha phase, generation of an impurity phase of the perovskite wet film is inhibited, a more uniform perovskite thin film can be obtained, and the perovskite ink is suitable for large-area thin film preparation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of perovskite solar cells, and in particular to a perovskite ink, a perovskite film and a battery device. Background Art

[0002] Organic-inorganic halide perovskite materials have great potential in new photovoltaic technologies due to their excellent performance. Among them, formamidinium lead iodide (FAPbI3) materials have a suitable band gap (~1.5 eV) and excellent thermal stability, but due to the relatively large volume of FA + Cations cause the phase structure to be unstable, and it is easy to transform from the active phase (α phase) of the cubic structure to the inactive phase (δ phase) of the hexagonal structure. To solve this problem, the alloying method of mixed cations and anions to adjust the Goldschmidt tolerance factor of the crystal is currently a more appropriate approach and a common method used in current high-efficiency devices. However, since the films of mixed anion and cation systems contain multiple components, due to complex phase behavior and crystallization dynamics, the resulting films are prone to multi-scale defects such as point defects, element segregation, and impurity phases. The heterogeneity of perovskite films further affects the photovoltaic performance and the long-term stability of the device.

[0003] Therefore, in mixed cation and anion systems, achieving pure phase and uniform perovskite films is a key issue in improving device efficiency and operational stability. Solution-processed perovskite films usually contain impurity phases, such as mixed solvent phase and δ phase, which need to be transformed into α phase during post-processing, but this phase transition process is accompanied by the generation of multi-scale defects. The preparation of uniform perovskite films is a key issue that needs to be solved in order to improve device efficiency and stability in mixed ion perovskite systems. This heterogeneity problem will be more serious when the perovskite film is scaled up. Therefore, further optimizing the composition of perovskite ink and regulating the nucleation and crystallization process of perovskite films are technical issues that need to be solved for the preparation of uniform large-area perovskite films. Summary of the invention

[0004] In order to solve the defects in the prior art, the present invention provides a perovskite ink, a perovskite film and a battery device. The perovskite ink of the present invention has a low aggregation barrier for perovskite nucleation, and the prepared perovskite wet film has only a pure perovskite α phase, which inhibits the generation of impurity phases in the perovskite wet film, and can obtain a more uniform perovskite film, which is suitable for large-area film preparation.

[0005] To achieve the above object, the present invention adopts the following technical solutions:

[0006] In a first aspect, the present invention provides a perovskite ink, the components of which include a formamidite-based perovskite material, a coordination solvent, and a nucleation regulator;

[0007] The coordination solvent is selected from one or more of N-methylpyrrolidone (NMP), dimethyl sulfoxide (DMSO), dimethylacetamide (DMA), N,N-dimethylformamide (DMF), 1,3-dimethyl-2-imidazolidinone (DMI), and γ-butyrolactone (GBL);

[0008] The nucleation regulator is selected from at least one of 3-aminomethylpyridine, 2-amino-5-fluoropyridine, 2-amino-4-fluoropyridine, 3-amino-5-fluoropyridine, 2-amino-6-fluoropyridine, 2-amino-5-chloropyridine, 3-amino-5-chloropyridine, 2-amino-5-bromopyridine, 2-amino-5-iodopyridine, 2-amino-5-methylpyridine, 2-amino-5-ethylpyridine, 2-amino-4-trifluoromethylpyridine, 2-amino-5-trifluoromethylpyridine, 3-amino-4-trifluoromethylpyridine, and 4-amino-2-trifluoromethylpyridine.

[0009] Preferably, the formamidinium perovskite material has a structure of ABX3, where A is composed of FA with a content of m + and other ions with a content of n. The other ions are K + , Rb + , Cs + , MA + , EA + , GA + , RNH 3+ or one or more of them, where m + n = 1, 0 < m ≤ 1, 0 ≤ n ≤ 1, B is Pb 2+ , Sn 2+ or one or two of them, and X is Cl - , Br - or I - or one or more of them.

[0010] Preferably, the content of the formamidinium perovskite material in the perovskite ink is 1.2 - 1.73 mol / L.

[0011] Preferably, the molar content of the nucleation regulator in the formamidinium perovskite material is 0.01 - 1 mol%.

[0012] Preferably, the coordination solvent is a mixed solvent of DMF and DMSO, and the volume ratio of DMF to DMSO is (1 - 9):(1 - 5).

[0013] In a second aspect, the present invention provides a method for preparing the perovskite ink, which includes mixing the formamidinium perovskite material, the nucleation regulator, and the coordination solvent to obtain it.

[0014] In a third aspect, the present invention provides a method for preparing a perovskite thin film, which is prepared from the perovskite ink.

[0015] Preferably, the method for preparing the perovskite film comprises the following steps:

[0016] (1) Cleaning the conductive glass substrate;

[0017] (2) preparing a hole transport layer on the conductive glass substrate;

[0018] (3) coating the perovskite ink on the hole transport layer and adding an anti-solvent for post-treatment to obtain a perovskite film.

[0019] Preferably, the treatment in step (3) includes but is not limited to annealing, natural volatilization in a protective atmosphere, and natural volatilization in an air atmosphere.

[0020] In a fourth aspect, the present invention provides a perovskite film prepared by the perovskite film preparation method.

[0021] Preferably, the perovskite film is a pure perovskite α phase.

[0022] In a fifth aspect, the present invention provides a battery device comprising the perovskite film.

[0023] Preferably, the structure of the battery device is, from bottom to top, the perovskite film, the passivation layer, the electron transport layer and the top electrode.

[0024] The beneficial effects of the present invention are:

[0025] The perovskite ink of the present invention can significantly reduce the repulsive interaction energy by adding a nucleation regulator, and the aggregation barrier of perovskite nucleation is lower, which is more conducive to aggregation nucleation.

[0026] The perovskite wet film prepared by the perovskite ink of the present invention has only pure perovskite α phase, inhibits the generation of impurity phase of the perovskite wet film, effectively enhances the crystallization of perovskite, improves the quality of the perovskite film, and the obtained perovskite film has a dense buried bottom interface, no hole formation is observed, and exhibits a narrower emission peak wavelength distribution. Moreover, the addition of a nucleation control agent can significantly change the nucleation behavior of perovskite, and the requirements for the film preparation process are reduced.

[0027] The perovskite film prepared by the perovskite ink provided by the present invention has better uniformity and is suitable for large-area film preparation. The battery device prepared by using the perovskite ink has better electrochemical performance and stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 The total interaction potential energy (Фtotal), van der Waals interaction energy (ФvdW) and repulsive interaction energy (Фrp) curves of the perovskite ink obtained in Example 1 and Comparative Example 1;

[0029] Figure 2 Schematic diagram of preparing perovskite film by spin coating;

[0030] Figure 3 X-ray diffraction (XRD) patterns of the perovskite wet films prepared in Example 2 and Comparative Example 2;

[0031] Figure 4 is the radial integrated intensity of the grazing incidence wide-angle X-ray scattering spectra (GIWAXS) of the perovskite films prepared in Example 2 and Comparative Example 2;

[0032] Figure 5 The scanning electron microscope (SEM) images of the buried interface of the perovskite film prepared in Example 2 and Comparative Example 2;

[0033] Figure 6 A mapping diagram of the photoluminescence (PL) emission wavelength of the perovskite film prepared in Example 2 and Comparative Example 2;

[0034] Figure 7 The scanning electron microscope (SEM) images of the perovskite wet films prepared in Example 3 and Comparative Example 3 after natural drying in a N2 atmosphere;

[0035] Figure 8 The SEM images of the perovskite wet films prepared in Example 4 and Comparative Example 4 after being naturally dried in air;

[0036] Fig. 9 The effective area obtained for Example 5 and Comparative Example 5 is 0.09 cm 2 JV curve of perovskite solar cells;

[0037] Fig.10 The effective area obtained for Example 5 and Comparative Example 5 is 655.2 cm 2 JV curve of perovskite solar cells;

[0038] Fig.11 The perovskite solar cells prepared in Example 7 and Comparative Example 7 were irradiated with continuous light (100 mW / cm 2 , continuous operation stability detection diagram of the initial maximum power point under white light LED lamp). DETAILED DESCRIPTION

[0039] In order to enable those skilled in the art to better understand the technical solution of the invention, the present invention is further described in detail below in conjunction with specific implementation methods.

[0040] The molar content of the nucleation regulator in the present invention is a ratio of the molar amount of the formamidinium-based perovskite material.

[0041] Example 1

[0042] This embodiment provides a method for preparing perovskite ink, and the preparation method is as follows:

[0043] The material is obtained by mixing the formamidinium-based perovskite material, the nucleation regulator and the coordination solvent.

[0044] Among them: (1) The system selection of formamidite-based perovskite materials (FA 0.98 MA 0.02 ) 0.95 Cs 0.05 Pb(I 0.98 Br 0.02 )3, specifically weighing 781.2 mg of lead iodide (PbI2), 277 mg of formamidinium hydroiodide (FAI), 13 mg of lead iodide (PbBr2), 11 mg of methylammonium bromide (MABr) and 22.5 mg of cesium iodide (CsI) into a container, and adding 5 mol% excess PbI2 and 15.5 mol% of methylammonium chloride (MACl); the content of the formamidinium-based perovskite material in the perovskite ink is 1.73 mol / L.

[0045] (2) The nucleation control agent is 2-amino-4-trifluoromethylpyridine (2A4TP), and its molar content can be 0.01-1 mol%. In this embodiment, the content is 0.5 mol%.

[0046] (3) The coordination solvent is a mixed solvent of DMF and DMSO, with a volume ratio of 1:5.

[0047] (4) The prepared perovskite ink can be used after being stirred at room temperature for 2 hours.

[0048] Comparative Example 1

[0049] This comparative example provides a method for preparing a perovskite ink, which is different from Example 1 in that the nucleation regulator 2A4TP is not added to the perovskite ink.

[0050] The potential energy of the perovskite ink obtained in Example 1 and Comparative Example 1 was tested, and the results are shown in the following table. Figure 1 . It can be seen that the total interaction potential energy (Фtotal) of colloidal particles condensing into nuclei is the sum of the van der Waals interaction energy (ФvdW) and the repulsive interaction energy (Фrp) between colloidal particles. Through dynamic light scattering, it is observed that the size of the colloidal particles in the perovskite ink after the introduction of 2A4TP has almost no change. The van der Waals interaction energy (ФvdW) between the colloidal particles in the perovskite ink is almost the same, but the repulsive interaction energy (Фrp) is significantly reduced. Therefore, compared with Example 1, the nucleation barrier of the perovskite ink in Comparative Example 1 without the addition of the nucleation regulator 2A4TP is higher, and it is not easy to aggregate and nucleate.

[0051] Example 2

[0052] Based on the perovskite ink prepared in Example 1, this example provides a method for preparing a perovskite film by spin coating:

[0053] (1) Preparation of transparent conductive substrate: First, cut the ITO conductive glass into the size required for the experiment (2.5 cm × 2.5 cm), then ultrasonically clean the glass for 15 minutes with glass cleaning solution, pure water, and ethanol respectively, and then blow dry with a nitrogen gun to obtain the conductive glass substrate used in the experiment.

[0054] (2) Preparation of hole transport layer: A 0.5 mg / ml (4-(2,7-dibromo-9,9-dimethylacridin-10(9H)-yl)butyl)phosphonic acid (DMAcPA) ethanol solution was spread on a conductive glass substrate at 3000 rpm in a nitrogen atmosphere for 30 seconds, and then annealed at 100°C for 10 minutes. Subsequently, an Al2O3 dispersion diluted with isopropanol was spin-coated on the DMAcPA film at 3000 rpm for 30 seconds and annealed at 100°C for 10 minutes.

[0055] (3) Preparation of perovskite wet film: The perovskite ink in Example 1 was spin coated onto the hole transport layer at a speed of 1000 rpm for 10 seconds, and then spin coated at a speed of 4000 rpm for 40 seconds. In the last 12 seconds, 200 μL of chlorobenzene (anti-solvent) was quickly added to the film. After the spin coating, a perovskite wet film was obtained.

[0056] (4) Preparation of perovskite film: The wet perovskite film is placed on a hot plate at 110°C and annealed for 20 minutes to obtain a perovskite film. The preparation diagram is shown in the figure below. Figure 2 shown.

[0057] Comparative Example 2

[0058] The same as Example 2, except that the perovskite ink used is the perovskite ink prepared in Comparative Example 1.

[0059] The perovskite wet films prepared in Example 2 and Comparative Example 2 were subjected to XRD testing. Figure 3 It can be seen that the sample without 2A4TP addition is a mixed structure of the solvent phase formed with the solvent, the perovskite active phase (α phase) and the inactive phase (δ phase), while the sample with 2A4TP addition is a pure α phase, indicating that the introduction of 2A4TP molecules can further reduce the transformation barrier of the perovskite from the δ phase to the active phase, and the perovskite active phase can be obtained at room temperature.

[0060] The perovskite films prepared in Example 2 and Comparative Example 2 were measured by GIWAXS. The results are shown in Figure 4It can be seen that in the sample without 2A4TP addition, a weak δ phase signal was detected, which indicates that the phase transition is not complete even after post-annealing without the help of 2A4TP molecules. In addition, the diffraction peak of the α(001) crystal plane of the sample with 2A4TP addition is narrower in half-height width (FWHM), with a FWHM of In contrast, the samples without 2A4TP addition were This reduction in FWHM indicates that the addition of 2A4TP can effectively enhance the crystallization of perovskite and improve the quality of perovskite films.

[0061] The buried interface of the perovskite film prepared in Example 2 and Comparative Example 2 was characterized by SEM. Figure 5 It can be seen that in the sample without 2A4TP, there are some large voids at the buried interface of the perovskite in contact with the hole transport layer, while the buried interface of the sample with 2A4TP is relatively dense and no hole formation is observed.

[0062] Figure 6 The figure is a mapping diagram of the photoluminescence (PL) emission wavelength of the perovskite films prepared in Example 2 and Comparative Example 2. It can be seen that the uniformity of the perovskite films prepared in Example 2 and Comparative Example 2 is further compared, and the photoluminescence (PL) of the micro area is measured under 532 nm pulsed laser irradiation using a confocal microscope. Compared with the sample without 2A4TP addition, the sample with 2A4TP added shows a narrower emission peak wavelength distribution.

[0063] These observations suggest that more uniform perovskite films can be obtained after the post-annealing process following the incorporation of 2A4TP.

[0064] Example 3

[0065] The same as Example 2, except that: Step (4) preparing the perovskite film: placing the perovskite wet film in a N2 atmosphere to volatilize naturally without annealing.

[0066] Comparative Example 3

[0067] The same as Example 3, except that the perovskite ink used is the perovskite ink prepared in Comparative Example 1.

[0068] Figure 7 The following are scanning electron microscope (SEM) images of the perovskite wet films prepared in Example 3 and Comparative Example 3 after natural drying in a N2 atmosphere. Figure 7 As shown, when the perovskite wet film is naturally dried in a N2 atmosphere, the sample without 2A4TP addition shows some large grains with some holes around the grains, while the sample with 2A4TP addition shows a dense film. The change in density is mainly due to the difference in perovskite nucleation.

[0069] Example 4

[0070] The same as Example 2, except that: Step (4) preparing the perovskite film: placing the wet perovskite film in an air atmosphere to volatilize naturally without annealing treatment, and the air humidity is less than 40%.

[0071] Comparative Example 4

[0072] The same as Example 4, except that the perovskite ink used is the perovskite ink prepared in Comparative Example 1.

[0073] Figure 8 The SEM images of the perovskite wet films prepared in Example 4 and Comparative Example 4 after natural drying in air. Figure 8 As shown, when the perovskite wet film is naturally dried in the air, the sample without 2A4TP shows large dendrites and more holes in the film, while the sample with 2A4TP shows a dense film like Example 3. This shows that the addition of the nucleation control agent 2A4TP can significantly change the nucleation behavior of perovskite and reduce the requirements for the film preparation process.

[0074] Example 5

[0075] Based on the perovskite film prepared in the above embodiment 2, this embodiment provides a method for preparing a photoelectric device, comprising the following steps:

[0076] (1) Preparation of passivation layer: Based on the perovskite film prepared in Example 2 above, PEABr solution (1 mg / mL isopropanol) was dynamically spin-coated onto the perovskite film at 3000 rpm for 30 seconds and annealed at 100°C for 10 minutes.

[0077] (2) Preparation of electron transport layer: 25 nm C was evaporated by thermal evaporation 60 The evaporation rate was controlled at 0.1-0.2 Å / s, followed by the deposition of 20 nm SnO2 by atomic layer deposition (ALD).

[0078] (3) Preparation of top electrode: A 100 nm silver electrode was evaporated by thermal evaporation, the evaporation rate was controlled at 0.8-1.0 angstroms / second, and the active area of ​​the battery was controlled at 0.09 square centimeters by a metal mask.

[0079] Comparative Example 5

[0080] The difference from Example 5 is that the nucleation regulator 2A4TP is not added to the perovskite ink.

[0081] Fig. 9 The effective area obtained for Example 5 and Comparative Example 5 is 0.09 cm 2 JV curve of perovskite solar cells. Fig. 9As shown in the figure, the best photoelectric conversion efficiency (PCE) of the sample with 2A4TP in reverse scanning is 24.59%, and the open circuit voltage (V OC ) is 1.143V, the short-circuit current density (J SC ) is 25.30mA / cm 2 , the fill factor (FF) is 85.05%. In contrast, the best photoelectric conversion efficiency of the sample without 2A4TP in reverse scanning is 23.79%, V OC is 1.129V, J SC 25.19 mA / cm 2 , FF is 83.60%. In addition, the hysteresis factor is also reduced from about 6% to about 2% after the introduction of 2A4TP, which can be attributed to the reduced interface defects and charge accumulation in the 2A4TP perovskite film.

[0082] Fig.10 The effective area obtained for Example 5 and Comparative Example 5 is 655.2 cm 2 JV curve of perovskite solar cells. Fig.10 As shown, the intensity used is 100mW / cm 2 The white light-emitting diodes (LEDs) were continuously illuminated, and the temperature of the device surface was about 50°C, and the operational stability of the packaged cells under the initial maximum power point bias was tested. The sample without 2A4TP was set at 0.96V, while the sample with 2A4TP was set at 1.00V. After 280 hours, the sample with 2A4TP retained 95.0% of its initial PCE. In contrast, the sample without 2A4TP showed more severe degradation, retaining only 85.6% of its initial PCE. The enhanced operational stability of the sample with 2A4TP can be attributed to more uniform and high-quality perovskite films with fewer impurity phases and defects.

[0083] Example 6

[0084] The present invention provides a method for preparing perovskite ink, and the preparation method is as follows:

[0085] The material is obtained by mixing the formamidinium-based perovskite material, the nucleation regulator and the coordination solvent.

[0086] Among them: (1) The system of formamidite-based perovskite material uses FA 0.83 Cs 0.17 PbI3, specifically weighing 553.2 mg of lead iodide (PbI2), 171.3 mg of formamidinium hydroiodide (FAI), 53 mg and cesium iodide (CsI) into a container, and adding 10 mol% of lead chloride PbCl2; the content of the formamidinium-based perovskite material in the perovskite ink is 1.2 mol / L.

[0087] (2) The nucleation regulator is 2-amino-4-trifluoromethylpyridine (2A4TP) with a molar content of 0.4 mol%.

[0088] (3) The coordination solvent is a mixed solvent of DMF and NMP in a ratio of 9:1.

[0089] (4) The prepared perovskite ink can be used after being stirred at room temperature for 2 hours.

[0090] Comparative Example 6

[0091] This comparative example provides a perovskite ink, which is different from Example 6 in that the nucleation regulator 2A4TP is not added to the perovskite ink.

[0092] Example 7

[0093] Based on the perovskite ink prepared in Example 6, the present invention provides a method for preparing a perovskite device by a coating method:

[0094] (1) Preparation of transparent conductive substrate: First, cut the ITO conductive glass into the size required for the experiment (30 cm × 30 cm), use laser cutting P1 line, and then ultrasonically clean the glass with glass cleaning liquid, pure water, and ethanol for 15 minutes respectively, and then blow dry with a nitrogen gun to obtain the conductive glass substrate used in the experiment.

[0095] (2) Preparation of hole transport layer: A 15 nm NiOx film was prepared by magnetron sputtering.

[0096] (3) Preparation of perovskite wet film: The perovskite ink in Example 6 is coated onto the hole transport layer by slit coating. The slit height is set to 200 μm. After the coating is completed, the sample is quickly transferred to a vacuum chamber to remove the solvent. The color of the sample quickly changes from transparent to dark brown, thereby obtaining a perovskite wet film.

[0097] (4) Preparation of perovskite film: annealing the wet perovskite film in air at 120° C. for 15 minutes to obtain a perovskite film, wherein the relative humidity of the environment is less than 40%.

[0098] (5) Preparation of passivation layer: 2 nm of LiF was evaporated by thermal evaporation, and the evaporation rate was controlled at 0.05 Å / s.

[0099] (6) Preparation of electron transport layer: Evaporate 25 nm of C by thermal evaporation 60 The evaporation rate was controlled at 0.1-0.2 Å / s, followed by deposition of 20 nm of SnO2 by atomic layer deposition (ALD), and laser cutting of the P2 line.

[0100] (7) Preparation of top electrode: Sputter a 100 nm copper electrode by magnetron sputtering and use laser cutting of P3 line.

[0101] The perovskite module prepared above consists of 42 sub-cells, and the effective area of ​​the perovskite module is 655.2 cm 2 .

[0102] Comparative Example 7

[0103] The same as Example 7, except that the perovskite ink used is the perovskite ink prepared in Comparative Example 6.

[0104] Fig.11 The perovskite solar cells prepared in Example 7 and Comparative Example 7 were irradiated with continuous light (100 mW / cm 2 , white LED lamp), the continuous operation stability of the initial maximum power point. Fig.11 As shown, the best PCE of the sample with 2A4TP added in the reverse scan is 16.12%, and the open circuit voltage V OC is 41.15V, J SC 0.54mA / cm 2 , FF is 72.23%. In contrast, the best PCE of the sample without 2A4TP addition in the reverse scan is 13.00%, V OC is 40.76V, J SC 0.52mA / cm 2 , FF is 60.97%.

[0105] By comparing Example 7 with Comparative Example 7, it can be seen that the introduction of the nucleation regulator 2A4TP is suitable for the scaled-up preparation of perovskite.

[0106] The above are only preferred embodiments of the present invention. It should be noted that the above preferred embodiments should not be regarded as limiting the present invention, and the protection scope of the present invention should be based on the scope defined by the claims. For ordinary technicians in this technical field, several improvements and modifications can be made without departing from the spirit and scope of the present invention, and these improvements and modifications should also be regarded as the protection scope of the present invention.

Claims

1. A perovskite ink, characterized in that: Its components include formamidite-based perovskite material, coordination solvent and nucleation regulator; The coordination solvent is selected from one or more of N-methylpyrrolidone (NMP), dimethyl sulfoxide (DMSO), dimethylacetamide (DMA), N,N-dimethylformamide (DMF), 1,3-dimethyl-2-imidazolidinone (DMI), and gamma-butyrolactone (GBL); The nucleation regulator is selected from at least one of 3-aminomethylpyridine, 2-amino-5-fluoropyridine, 2-amino-4-fluoropyridine, 3-amino-5-fluoropyridine, 2-amino-6-fluoropyridine, 2-amino-5-chloropyridine, 3-amino-5-chloropyridine, 2-amino-5-bromopyridine, 2-amino-5-iodine, 2-amino-5-methylpyridine, 2-amino-5-ethylpyridine, 2-amino-4-trifluoromethylpyridine, 2-amino-5-trifluoromethylpyridine, 3-amino-4-trifluoromethylpyridine, and 4-amino-2-trifluoromethylpyridine.

2. The perovskite ink according to claim 1, characterized in that The content of the formamidinium-based perovskite material in the perovskite ink is 1.2 to 1.73 mol / L.

3. The perovskite ink according to claim 1, characterized in that The molar content of the nucleation regulator in the formamidite-based perovskite material is 0.01 to 1 mol%.

4. The perovskite ink according to any one of claims 1 to 3, characterized in that: The formamidinium perovskite material has a structure of ABX3, where A is composed of FA with a content of m + and other ions with a content of n. The other ions are K + , Rb + , Cs + , MA + , EA + , GA + , RNH 3+ or one or more of them, where m + n = 1, 0 < m ≤ 1, 0 ≤ n ≤ 1, B is Pb 2+ , Sn 2+ or one or two of them, and X is Cl - , Br - or I - or one or more of them.

5. A method for preparing the perovskite ink according to any one of claims 1 to 4, characterized in that: The method comprises mixing a formamidine-based perovskite material, a nucleation regulator and a coordination solvent.

6. A method for preparing a perovskite film, characterized in that: Prepared from the perovskite ink according to any one of claims 1 to 4.

7. The method for preparing a perovskite thin film according to claim 6, characterized in that: The following steps are involved: (1) Cleaning the conductive glass substrate; (2) preparing a hole transport layer on the conductive glass substrate; (3) The perovskite ink according to any one of claims 1 to 4 is coated on the hole transport layer and then an anti-solvent is added for post-treatment to obtain a perovskite film.

8. The method for preparing a perovskite thin film according to claim 7, characterized in that: The treatment in step (3) includes but is not limited to annealing, natural volatilization in a protective atmosphere, and natural volatilization in an air atmosphere.

9. A perovskite film prepared by the method for preparing a perovskite film according to any one of claims 6 to 8.

10. A battery device, characterized in that: Comprising the perovskite film as described in claim 9.